MULTI-SECTOR COLLABORATION FOR SUSTAINABLE TOURISM MANAGEMENT: INSIGHTS FROM CENTRAL LOMBOK REGENCY, INDONESIA - Sari, Ananda Rivaldo (VISIONER : Jurnal Pemerintahan Daerah di Indonesia, 2024)
This literature review critically examines the dynamics of multi-sector collaboration in sustainable tourism management, specifically emphasizing insights from Central Lombok Regency, Indonesia. Sustainable tourism demands robust cooperation across public institutions, private enterprises, and local communities; however, implementing effective collaborative frameworks remains a persistent challenge. Existing literature underscores issues such as inadequate coordination among stakeholders, varying priorities, and resource disparities, which collectively impede collaborative progress. Conversely, several studies identify innovative practices and mechanisms that successfully promote multi-stakeholder partnerships, enhancing environmental conservation, economic development, and social inclusivity. Central Lombok presents a valuable case study due to its strategic importance as an emerging sustainable tourism destination, where inter-sectoral synergy significantly influences tourism outcomes. The findings highlight the critical role local governments play in initiating and sustaining multi-sector partnerships through policy interventions, clear governance structures, and continuous stakeholder engagement. Additionally, this review underscores the necessity of aligning stakeholders' diverse objectives and establishing transparent communication channels to resolve conflicts and foster trust. Further exploration of literature reveals that stakeholder capacity building and community empowerment serve as essential ingredients for long-term sustainability. This paper identifies gaps in existing research, recommending focused empirical studies to strengthen theoretical frameworks guiding multi-sector collaboration in sustainable tourism management contexts.